Utilizing Social Media TikTok @perpusbogor to Increase Library Visit Interest - Faniya, Yunda; Pramudyo, Gani Nur (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: The low level of public interest in visiting libraries has encouraged libraries to innovate their promotional strategies by utilizing social media platforms. TikTok, being one of the most popular social media platforms among the public, is now also used by libraries to promote their services, as exemplified by the Bogor Library through its TikTok account @perpusbogor.Objective: This study aims to examine the influence of the utilization of TikTok @perpusbogor on fostering interest in visiting the library.Methods: A quantitative research approach was applied. Data were collected through questionnaires distributed directly to visitors at the Bogor Library. The data were analyzed using SPSS version 25.Results: The results revealed that the majority of respondents are university students aged 22-24. They primarily use the @perpusbogor TikTok account for informational purposes. This finding suggests a positive relationship between information-oriented social media use and high library visitation, driven by a strong sense of curiosity. Overall, social media has proven to be an effective promotional tool that directly caters to the needs of library patrons.Conclusion: Furthermore, the overall utilization of TikTok @perpusbogor to enhance library visit interest was categorized as high, with an average mean score of 3.82. Information seeking emerged as the most dominant aspect of social media utilization. Recommendations to further optimize TikTok usage include providing librarian training on social media optimization, developing strategies for creating engaging content, and ensuring institutional support from the library management.